Sanksi Pidana Terhadap Pelaku Pemalsuan Surat Rapid Test di Masa Pandemi Covid- 19 - I Kadek Candra Karunia Bagiarta Putra Sugiantara; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2021)
The outbreak of the Covid-19 virus has caused the Indonesian government to take a serious policy in tackling the spread of this virus by imposing regional restrictions. This policy has led to the falsification of the COVID-19 rapid test certificate and the collection of rapid management fees at inflated prices. The purpose of this study is to uncover the criminal act of counterfeiting a rapid test letter and the legal sanctions for counterfeiting a rapid test letter. This research is a type of normative legal research with statutory law and factual law. Sources of legal materials used in the form of primary and secondary legal materials. The technique of collecting legal materials in this research is recording and recording which is then analyzed deductively and inductively logic. The results of the study reveal that letter falsification is regulated in Articles 263 to 267 of the Criminal Code, besides that it is also regulated in Article 7 of the medical code of ethics. If the doctor is proven to have committed the falsification himself, then the liability is punishable by a maximum of 4 years and administrative sanctions.